2011
DOI: 10.1016/j.molcel.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Deficiency and Mitochondrial Protein Hyperacetylation Accelerate the Development of the Metabolic Syndrome

Abstract: SUMMARY Acetylation is increasingly recognized as an important metabolic regulatory post-translational protein modification, yet the metabolic consequence of mitochondrial protein hyperacetylation is unknown. We find that high-fat diet (HFD) feeding induces hepatic mitochondrial protein hyperacetylation in mice and downregulation of the major mitochondrial protein deacetylase SIRT3. Mice lacking SIRT3 (SIRT3KO) placed on a HFD show accelerated obesity, insulin resistance, hyperlipidemia, and steatohepatitis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
718
15
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 715 publications
(776 citation statements)
references
References 78 publications
40
718
15
3
Order By: Relevance
“…Thus, SIRT3 may also play a role in mediating islet compensation of insulin resistance, such that only when SIRT3 levels decrease can impaired islet function and type 2 diabetes occur. Increased islet SIRT3 levels are consistent with other studies in skeletal muscle and liver, which reported increases in mitochondrial proteins, including SIRT3, in earlier stages of high-fat feeding [48,49]. We also demonstrated marked reductions in SIRT3 levels in islets isolated from animals that had been fasted for 24 h. This is at odds with findings in liver, where SIRT3 levels increased following a 24 h fast [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, SIRT3 may also play a role in mediating islet compensation of insulin resistance, such that only when SIRT3 levels decrease can impaired islet function and type 2 diabetes occur. Increased islet SIRT3 levels are consistent with other studies in skeletal muscle and liver, which reported increases in mitochondrial proteins, including SIRT3, in earlier stages of high-fat feeding [48,49]. We also demonstrated marked reductions in SIRT3 levels in islets isolated from animals that had been fasted for 24 h. This is at odds with findings in liver, where SIRT3 levels increased following a 24 h fast [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Numerous mitochondrial proteins are subject to reversible Lys acetylation, many of which are directly involved in metabolic homeostasis (Anderson & Hirschey, 2012; Kim et al, 2006). Thus, it is not surprising to observe that hyperacetylation of mitochondrial proteins is often observed in obesity (Hirschey et al., 2011) and chronic alcohol consumption (Shepard, Tuma & Tuma, 2010). Our results further support that mitochondrial protein modification by the acetylation/deacetylation reaction is a key event governing cellular response to ischemic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Hirschey and co‐workers (Hirschey et al. 2011), feeding mice a high‐fat diet for 13 weeks reduced liver SIRT3 protein content and significantly increased hepatic mitochondrial protein acetylation as compared to mice fed standard diet. The authors attributed the loss of SIRT3 protein to the reduction in PGC‐1 α , a known regulator of SIRT3 (Kong et al.…”
Section: Discussionmentioning
confidence: 99%